2019
DOI: 10.1080/10888438.2019.1698583
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Second and Third Graders’ Reading Comprehension Gains: Observing Students’ and Classmates Talk During Literacy Instruction Using COLT

Abstract: This paper introduces a new observation system that is designed to investigate students' and teachers' talk during literacy instruction, Creating Opportunities to Learn from Text (COLT). Using video-recorded observations of 2 nd-3 rd grade literacy instruction (N=51 classrooms, 337 students, 151 observations), we found that nine types of student talk ranged from using non-verbal gestures to generating new ideas. The more a student talked, the greater were his/her reading comprehension (RC) gains. Classmate tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Across settings, studies have also conceptualized teacher language as use of open-ended language to encourage interaction and close-ended language to elicit specific information (Walsh, 2002;Westgate & Hughes, 1997). These studies have primarily described the language environment, examining the relation between features of teachers' talk and students' communication (Connor et al, 2020;Jadallah et al, 2011;Liu, 2008;Sadler & Mogford-Bevan, 1997;Sparapani et al, 2020). Studies have found that teachers' use of open-ended language, such as asking open-ended questions and making contextual statements is associated with student participation (e.g., Milburn et al, 2014), generative or interactive talk (Connor et al, 2020;Duke et al, 2011;Reznitskaya et al, 2009), and on-topic initiations (Mercer, 1996;Walsh, 2002).…”
Section: Conceptualizing the Teacher Language Constructmentioning
confidence: 99%
See 4 more Smart Citations
“…Across settings, studies have also conceptualized teacher language as use of open-ended language to encourage interaction and close-ended language to elicit specific information (Walsh, 2002;Westgate & Hughes, 1997). These studies have primarily described the language environment, examining the relation between features of teachers' talk and students' communication (Connor et al, 2020;Jadallah et al, 2011;Liu, 2008;Sadler & Mogford-Bevan, 1997;Sparapani et al, 2020). Studies have found that teachers' use of open-ended language, such as asking open-ended questions and making contextual statements is associated with student participation (e.g., Milburn et al, 2014), generative or interactive talk (Connor et al, 2020;Duke et al, 2011;Reznitskaya et al, 2009), and on-topic initiations (Mercer, 1996;Walsh, 2002).…”
Section: Conceptualizing the Teacher Language Constructmentioning
confidence: 99%
“…These studies have primarily described the language environment, examining the relation between features of teachers' talk and students' communication (Connor et al, 2020;Jadallah et al, 2011;Liu, 2008;Sadler & Mogford-Bevan, 1997;Sparapani et al, 2020). Studies have found that teachers' use of open-ended language, such as asking open-ended questions and making contextual statements is associated with student participation (e.g., Milburn et al, 2014), generative or interactive talk (Connor et al, 2020;Duke et al, 2011;Reznitskaya et al, 2009), and on-topic initiations (Mercer, 1996;Walsh, 2002). Open-ended language has also been linked with higher order thinking and academic achievement (Burchinal et al, 2008;Connor et al, 2020).…”
Section: Conceptualizing the Teacher Language Constructmentioning
confidence: 99%
See 3 more Smart Citations